2017
DOI: 10.1007/s00520-017-3700-1
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of a percutaneous endoscopic gastrostomy (PEG) for decompression in patients with malignant gastrointestinal obstruction

Abstract: The PEG for decompression significantly reduces vomiting and nausea in patients with malignant gastrointestinal obstruction (p < 0.001). Minor complications are common and should be discussed prior to the intervention. Nevertheless, the PEG appears to demonstrate prevailing benefits in comparison to the risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 19 publications
(48 reference statements)
2
26
0
2
Order By: Relevance
“…10,13 However, a recent study found that ascites was not significant for the development of infective complications, but it is an independent risk factor for stomal leakage and insufficient drainage. 15 It also found no association between ascites and technical success of the procedure. 15 Overall, it appears that the presence of ascites should not be considered an absolute contraindication for insertion of percutaneous drainage gastrostomy tube to relieve MBO, even though there is a slightly higher chance of minor complications such as stomal leakage postprocedure in these patients.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…10,13 However, a recent study found that ascites was not significant for the development of infective complications, but it is an independent risk factor for stomal leakage and insufficient drainage. 15 It also found no association between ascites and technical success of the procedure. 15 Overall, it appears that the presence of ascites should not be considered an absolute contraindication for insertion of percutaneous drainage gastrostomy tube to relieve MBO, even though there is a slightly higher chance of minor complications such as stomal leakage postprocedure in these patients.…”
Section: Discussionmentioning
confidence: 92%
“…These studies indicate that drainage percutaneous gastrostomy tubes can technically be placed despite the presence of ascites in patients with MBO; however, longitudinal outcomes and complications are lacking (Table 2). 9,10,[12][13][14][15][16][17][18]23,24,26,28 Although the majority did not drain the ascites, some studies advocate predrainage of ascites to facilitate insertion and prevent associated complications. 12,13,16 One study found no association between the presence of ascites and survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Backward migration to the stomach is a common event, which may be reduced if the tip is initially placed beyond the ligament of Treitz [20]. In order to reduce repeated manipulation and the risk of gastric migration of the jejunal tube, the connection of a drainage PEG to the feeding PEG-J was proposed for GOO patients [42,43].…”
Section: Peg With Jejunal Extension Andmentioning
confidence: 99%